1384 Managing Peri-Orbital and Orbital Cellulitis: A New Multi-Specialty Care Pathway. (12th October 2021) - Karim, S; Halliday, C; Patel, K; Acharya, V
Abstract: Aim: 1) To review current practice in the diagnosis and management of peri-orbital and orbital cellulitis in children at a London University Teaching Hospital. 2) To design and implement a streamlined, multi-specialty care pathway to improve the quality of care. Background: Clinical differentiation between peri-orbital cellulitis and orbital cellulitis is often difficult, especially in young children. Early recognition and aggressive, multi-specialty treatment are required in order to prevent any vision and life-threatening sequelae. Method: A retrospective case note analysis was performed for all paediatric patients with suspected peri-orbital or orbital cellulitis over a nineteen-month period. Extensive literature review was undertaken to ascertain current best practice in diagnosis and management. A streamlined, multi-specialty care pathway was developed, ratified by specialist departments, and introduced to optimise safety and quality of care. Results: The results correlate with trends found in recent literature. 94.3% of patients had a blood culture taken with only 9.1% being positive. There were inadequate eye (37.1%) and endonasal (17.1%) cultures. Wide variation was noted in the criteria for imaging and in the antibiotic regimen used. 25.7% of patients received any nasal treatment. Suboptimal specialist review was identified in both orbital (60%) and peri-orbital (50.0%) cellulitis. Conclusions: The new care pathway clearly informs investigation and empiric treatment based on initial risk stratification. The paediatric team is now the main, named care provider responsible for coordinating specialist input.